A practitioner`s guide to isometric hip adduction and abduction test selection: Maximal force, asymmetry, and muscle activity comparisons between assessment positions - Secomb, J. L. (Journal of Sports Sciences, 2024)
The purpose of this study was to compare maximal adduction (ADD) and abduction (ABD) force, ADD to ABD ratio (ADD:ABD), inter-limb asymmetries and muscle activity between five isometric hip strength assessment positions. Twenty male athletes performed the following positions: seated (SE), supine at knees with 0° hip flexion (SK0°) and 45° hip flexion (SK45°), and supine at ankles bilaterally (SABI) and unilaterally (SAUNI). Normalised muscle activity (%EMGmax) of adductor longus (ADDLONG), gracilis (GRAC), gluteus medius (GMED), sartorius (SAR), and lower rectus abdominis (RECABD) were also assessed. Significant main effects of assessment position were identified for relative peak force (rPF) and torque (rT), ADD:ABD, ADD asymmetry, and %EMGmax. Significantly greater ADD and ABD rPF and rT were observed in SE and SK45° compared to SABI and SAUNI. SK45° elicited the highest ADDLONG and GRAC %EMGmax during ADD, with SE and SK45° evoking the highest GMED %EMGmax during ABD. SK0° exhibited significantly higher ADD:ABD compared to all positions except SAUNI. ADD asymmetry was significantly largest in SAUNI, and RECABD %EMGmax was highest in SABI during ADD. This data can inform selection of assessment positions based on whether the primary measures of interest are maximal force and muscle activity, or identifying asymmetries.